2019
DOI: 10.1177/1359105319890397
|View full text |Cite
|
Sign up to set email alerts
|

Causative factors of eating problems among adolescents with type 1 diabetes mellitus: A qualitative study

Abstract: Adolescents with type 1 diabetes mellitus are prone to have eating problems. This study aimed to determine factors of eating problems among this population in University Malaya Medical Centre. Fifteen adolescents who scored more than 20 marks in the Diabetes Eating Problem Survey – Revised questionnaire were invited for an in-depth interview. Questions were asked based on their questionnaire’s response. The interview sessions were recorded, transcribed verbatim, and thematic analysis was used. Five main themes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
5
0
2
Order By: Relevance
“…In contrast to the male described by Morris [62], the males described by Szmukler and Russell [80] and Szmukler [79] reported the deliberate restriction and/or omission of insulin among other disordered eating behaviours (e.g., restriction of food intake, purging). McConnell et al's [33] case study reported the deliberate omission of insulin by a 9-year-old male in response to "unpleasant situations" rather than for weight and/or shape control, while Sien et al [63] had no males who restricted and/or omitted insulin for weight and/ or shape control.…”
Section: Qualitative Studiesmentioning
confidence: 99%
“…In contrast to the male described by Morris [62], the males described by Szmukler and Russell [80] and Szmukler [79] reported the deliberate restriction and/or omission of insulin among other disordered eating behaviours (e.g., restriction of food intake, purging). McConnell et al's [33] case study reported the deliberate omission of insulin by a 9-year-old male in response to "unpleasant situations" rather than for weight and/or shape control, while Sien et al [63] had no males who restricted and/or omitted insulin for weight and/ or shape control.…”
Section: Qualitative Studiesmentioning
confidence: 99%
“…Valgymo problemų atsiradimą skatina aplinkoje patiriamas psichologinis spaudimas: mokykloje, tėvų, bendraamžių, baimė būti kritikuojamiems šeimos bei draugų. Mokykloje patiriamas stresas lemia, kad paaugliai maitinasi nereguliariai arba praleidžia valgymus [18]. Stebima, kad I tipo diabetu sergantys ir sutrikusios valgymo elgsenos paaugliai yra žemesnio socioekonominio statuso, tad žemas šeimos išsilavinimas ir darbinė veikla yra įspėjamasis ženklas I tipo diabetu sergančių paauglių sutrikusiai valgymo elgsenai išsivystyti [17,19].…”
Section: Tyrimo Rezultatai Ir Jų Aptarimasunclassified
“…In some studies, it was noted that the ratio of the Indian population was similar or equal to the Chinese population (Hamzah et al, 2019) and at times greater than the Chinese population (Gan et al, 2018;Tan et al, 2022). Studies which were specific to target groups included one study involving the Chinese and Indian population (Lek et al, 2018), one study concerning the Orang Asli/indigenous population (Gan et al, 2020) and two studies focusing on such specific groups as diabetic patients (Sien et al, 2020) and hypertension patients (Liew et al, 2019). The differences in the composition of populations embedded in the studies were caused by the differentiating sampling methodology chosen for the studies.…”
Section: Measurementmentioning
confidence: 99%